2023
DOI: 10.1111/1750-3841.16752
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of pectin from watermelon and pomegranate peels with different methods and its application in ice cream as an emulsifier

Esra Fırat,
Nurcan Koca,
Figen Kaymak‐Ertekin

Abstract: Pectin extraction from watermelon peel (WP) and pomegranate peel (PP) was carried out using three different extraction methods: classical solvent extraction (CSE), ultrasound‐assisted extraction (UAE), and microwave‐assisted extraction (MAE). Extraction parameters (pH, temperature, time, and speed/amplitude/power) were optimized to target maximum crude pectin yield (CPY), while the sample‐to‐solvent ratio (SS) was determined to be fixed at 1:10 w/v at all experiments. CPY was increased by low pH, high temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 106 publications
(161 reference statements)
0
0
0
Order By: Relevance
“…Yang et al [15] achieved a pomegranate pectin yield of 8.5% using hot water at 86 • C and pH 1.7 for 80 min. Fırat et al [16] found 11.56% for pomegranate pectin yield using ultrasound-assisted extraction at pH 1.5, 69 • C, and 29 min using HCl. Furthermore, dietary consumption of pectin has been shown to exhibit favorable effects in the prevention of chronic diseases such as diabetes and heart disease and to exert potential anticancer properties, which is supported by evidence from cellular and animal studies, human clinical trials, and toxicity evaluations [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [15] achieved a pomegranate pectin yield of 8.5% using hot water at 86 • C and pH 1.7 for 80 min. Fırat et al [16] found 11.56% for pomegranate pectin yield using ultrasound-assisted extraction at pH 1.5, 69 • C, and 29 min using HCl. Furthermore, dietary consumption of pectin has been shown to exhibit favorable effects in the prevention of chronic diseases such as diabetes and heart disease and to exert potential anticancer properties, which is supported by evidence from cellular and animal studies, human clinical trials, and toxicity evaluations [17,18].…”
Section: Introductionmentioning
confidence: 99%